Psoriasis is associated with pleiotropic susceptibility loci identified in type II diabetes and Crohn disease. Issue 2 (9th November 2007) - Wolf, N; Quaranta, M; Prescott, N J; Allen, M; Smith, R; Burden, A D; Worthington, J; Griffiths, C E M; Mathew, C G; Barker, J N; Capon, F; Trembath, R C
Abstract : Background: Psoriasis is an immune-mediated skin disorder that is inherited as a multifactorial trait. Linkage analyses have clearly mapped a primary disease susceptibility locus to the major histocompatibility complex (MHC) region on chromosome 6p21. More recently, whole-genome association studies have identified two non-MHC disease genes ( IL12B and IL23R ), both of which also confer susceptibility to Crohn disease (CD). Objective and methods: To ascertain the genetic overlap between these two inflammatory conditions further, we investigated 15 CD-associated loci in a psoriasis case–control dataset. Results: The analysis of 1256 patients and 2938 unrelated controls found significant associations for loci mapping to chromosomes 1q24 (rs12035082, p = 0.009), 6p22 (rs6908425, p = 0.00015) and 21q22 (rs2836754, p = 0.0003). Notably, the marker showing the strongest phenotypic effect (rs6908425) maps to CDKAL1, a gene also associated with type 2 diabetes. Conclusions: These results substantiate emerging evidence for a pleiotropic role for s genes that contribute to the pathogenesis of immune-mediated disorders.